2019
DOI: 10.1111/nicc.12484
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic and cardiovascular surgery patients: Intensive care unit experiences

Abstract: BackgroundIntensive care units are stressful places where patients experience physical and psychological discomfort. Understanding the experience of these patients regarding nursing care is very important.Aims and objectivesTo determine the intensive care experiences of thoracic and cardiovascular surgery patients and the factors that affect them.DesignThe research consists of two phases: quantitative and qualitative.MethodsThis was a descriptive and cross‐sectional study. Its research sample comprised 100 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
2
24
0
1
Order By: Relevance
“…Study characteristics showed that the investigations were performed in diverse international regions, with a median patient sample size of 76.5. Gender distribution and age were similar to those of other ICU studies that had applied questionnaires or interviews to investigate the experience of ICU patients (e.g., [9,10,28,[65][66][67][68][69][70][71][72][73][74][75]): With an average rate of 64%, most of the patients were men and had a median age of 55.7 years. There were 13 studies that had also included stressor ratings of HCPs who were mostly women (68.4%) and were between 30 and 40 years of age.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Study characteristics showed that the investigations were performed in diverse international regions, with a median patient sample size of 76.5. Gender distribution and age were similar to those of other ICU studies that had applied questionnaires or interviews to investigate the experience of ICU patients (e.g., [9,10,28,[65][66][67][68][69][70][71][72][73][74][75]): With an average rate of 64%, most of the patients were men and had a median age of 55.7 years. There were 13 studies that had also included stressor ratings of HCPs who were mostly women (68.4%) and were between 30 and 40 years of age.…”
Section: Discussionsupporting
confidence: 68%
“…However, findings showed that patients sometimes have memory problems concerning their ICU treatment. Several studies found indeed that between 15% and 38% of ICU patients did not remember their experiences on ICU, and approximately 50% had difficulties to distinguish dreams and reality [1,5,9,12,27,28,59,60,81]. This means that stress perception of this considerably large group of ICU patients has either been distorted or has not been included in the reviewed questionnaire investigations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some supportive approaches are recommended for patients in the intensive care unit to feel safe and have positive experiences ( 15 ). The physical discomfort and negative emotions experienced by patients in the intensive care setting can be reduced with effective healthcare professionals ( 9 ). Therefore, it is important that healthcare professionals are aware of patients’ experiences to meet the needs of patients and prevent physiological and psychological morbidities ( 11 , 15 ).…”
Section: Introductionmentioning
confidence: 99%